Diabetes care: who are the experts?. Issue 4 (December 1992) - Hares, T; Spencer, J; Gallagher, M; Bradshaw, C; Webb, I
Abstract : OBJECTIVES–To identify issues that patients and professionals consider important in diabetes care and differences in their priorities for care and to determine patients' and professionals' judgements of the relative importance of their chosen priorities. DESIGN–Structured group interviews using the nominal group technique. SETTING–Five district health authorities on Tyneside. SUBJECTS–Five nominal groups: expert (seven), non-expert (seven) health care professionals; insulin dependent (four), non-insulin dependent patients (eight); and carers of diabetic patients (eight). MAIN MEASURES–Items important in diabetes care to each nominal group (themes of care), ranked into a series of "top 10" items for each group, and allocated a score according to relative importance to individual members; scores were standardised by individual weighting and group weighting for comparison within and between groups. RESULTS–Patients and professionals agreed that information given to patients, interaction between professionals and patients, patient autonomy, and access were important for good diabetes care, but the importance assigned to each differed. Thus the professionals emphasised empathy and aspects of good communication and patients the desire to know enough to live a "normal" life. Differences were also found within the patient groups; these related to changes in patients' needs at specific points in the development of their illness and in their orientations to care. CONCLUSION–Patients differ from professionals in their orientation to diabetes care, and they can, and should, be involved in setting priorities for care. Since these priorities are dynamic further work is needed to explore the nature of patient satisfaction with diabetes care.